Detection of Ureaplasma parvum in amniotic fluids via reanalysis of prenatal copy number variation sequencing data: an exploratory study - Wang, Guan; Chen, Weifen; Chen, Xiaodan; Hou, Hongying; Zhang, Jun; Han, Zhenyan (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundDetecting microbes in amniotic fluids via amniocentesis represents the standard method for diagnosing intrauterine infections. Given its similarity to metagenomic next-generation sequencing, copy number variation sequencing (CNV-seq) data may also contain microbial sequences. This exploratory study aimed to investigate the feasibility of prenatal CNV-seq for detecting Ureaplasma parvum (U. parvum) in amniotic fluids and to evaluate the pregnancy outcomes in U. parvum-positive cases.MethodsThis retrospective study enrolled 2419 singleton pregnant women who underwent genetic amniocentesis for fetal CNV-seq testing and completed the follow-up with documented pregnancy outcomes. The CNV-seq data were reanalyzed to extract the read counts of U. parvum from each sample’s raw data, and reads per million (RPM) was used to quantify its relative abundance.ResultsThe prevalence of asymptomatic intrauterine U. parvum positivity in this cohort was 1.4% (33/2419), with read counts ranging 1 to 30423 and RPM from 0.09 to 3580.65 by reanalysis of CNV-seq data. There was a statistically significantly higher risk for early spontaneous preterm labor (<32 gestational weeks; P<0.001) and preterm premature rupture of the membranes (P<0.001) in women with positive U. parvum compared to negative cases. Among U. parvum positive cases, six cases (6/33, 18.2%) had relatively higher read counts ranging from 2483 to 30423, with corresponding RPM of 406.45 to 3580.65. Adverse pregnancy outcomes were exclusively observed among women with high reads of U. parvum as opposed to those with low reads. Four cases with high U. parvum reads in amniotic fluids, not treated with antibiotics, showed a latency period of 6 to 10 weeks from positive detection to the onset of clinical manifestations.ConclusionsCNV-seq may be a feasible method for detecting intraamniotic U. parvum infection. High abundance of asymptomatic U. parvum in amniotic fluids are statistically associated with adverse pregnancy outcomes, highlighting its importance in preliminary screening.